A Novel Inter Connection of DFIG with Grid in Separate Excitation SMES System with Fuzzy Logic Control - A. Kavitha; A. V. Suresh (Institute of Advanced Engineering and Science, 2015)
The use of doubly fed induction generators (DFIGs) in wind turbines has become quite common over the last few years. DFIG wind turbine is an integrated part of distributed generation system. This paper presents a Fuzzy based controller SMES unit in DFIG for improving the ac output on grid side. The excitation system is composed of the rotor-side converter, the grid-side converter, the dc chopper and the superconducting magnet. The superconducting magnet is connected with the dc side of the two converters, which can handle the active power transfer with the rotor of DFIG and the power grid independently, even thou Sutton small fluctuations are occur in active power on AC side. For smoothening the AC output power waveform a Fuzzy based controller is introduced in SMES controller unit, which implemented using simulation developed in MATLAB/ SIMULINK 7.2 version. The model of the FUZZY controlled SMES based excitation system for DFIG is established, and the simulation tests are performed to evaluate the system performance.